2021
DOI: 10.3390/antiox10071089
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming with Brassinosteroids Alleviates Chromium Stress in Rice Cultivars via Improving ROS Metabolism and Antioxidant Defense Response at Biochemical and Molecular Levels

Abstract: This research was performed to explore the vital role of seed priming with a 0.01 µM concentration of brassinosteroids (EBL) to alleviate the adverse effects of Cr (100 µM) in two different rice cultivars. Seed priming with EBL significantly enhanced the germination attributes (germination percentage, germination energy, germination index, and vigor index, etc.), photosynthetic rate as well as plant growth (shoot and root length including the fresh and dry weight) under Cr toxicity as compared to the plants pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 62 publications
(75 reference statements)
2
34
0
Order By: Relevance
“…Cr cause severe phytotoxic effects on plants growth, and biomass by decreasing the photosynthetic rate, disturbing mineral uptake balance, and increasing Cr uptake ( Singh et al, 2021 ). It is noticed that Cr stress cause reduction in seed germination rate, and disturb the antioxidative defense mechanism as well ( Basit et al, 2021a , Basit et al, 2021c , Basit et al, 2022 ). It is revealed that Cr uptake, and translocation minimize the germination, and growth ratio, negatively effects on chlorophyll pigments production, and PSII system, and increase electrolyte leakage by stimulating the ROS generation ( Wakeel et al, 2020 ), and ultimately crop yield is compromised.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cr cause severe phytotoxic effects on plants growth, and biomass by decreasing the photosynthetic rate, disturbing mineral uptake balance, and increasing Cr uptake ( Singh et al, 2021 ). It is noticed that Cr stress cause reduction in seed germination rate, and disturb the antioxidative defense mechanism as well ( Basit et al, 2021a , Basit et al, 2021c , Basit et al, 2022 ). It is revealed that Cr uptake, and translocation minimize the germination, and growth ratio, negatively effects on chlorophyll pigments production, and PSII system, and increase electrolyte leakage by stimulating the ROS generation ( Wakeel et al, 2020 ), and ultimately crop yield is compromised.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it is noticed that nutrient, and Cr uptake competition cause Cr binding with carrier channels and plasma membrane, and weakened the H + ATPase activity ( Habiba et al, 2019 ). A current study represented that Cr-induced phytotoxicity reduce plants biomass, and photosynthetic ability by enhancing the stress markers such as malondialdehyde (MDA), and hydrogen peroxide (H 2 O 2 ), electrolyte leakage (EL), and Cr uptake inside Oryza sativa ( Basit et al, 2021a ), Sesbania sesban ( Din et al, 2020 ), Brassica napus ( Ulhassan et al, 2019b ), tomato ( Alamri et al, 2020 ), Spinacia oleracea ( Zaheer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytohormone-based seed priming also proved to be effective against abiotic stress. Basit et al [21] concluded that seed priming with brassinosteroids (EBL) could be adopted as a promising strategy to enhance rice growth by copping the toxic effect of chromium (Cr). They [21] revealed that seed priming with a low dose (0.01 µM) of EBL could alleviate the adverse effects of Cr in two different rice cultivars.…”
mentioning
confidence: 99%
“…Basit et al [21] concluded that seed priming with brassinosteroids (EBL) could be adopted as a promising strategy to enhance rice growth by copping the toxic effect of chromium (Cr). They [21] revealed that seed priming with a low dose (0.01 µM) of EBL could alleviate the adverse effects of Cr in two different rice cultivars. Seed priming with EBL stimulatingly increased antioxidant enzyme activities to scavenge ROS production under Cr stress.…”
mentioning
confidence: 99%